Methods for solving linear programming problems with fuzzy parameters - Kaur, Jagdeep (My University, 2012)
In this thesis, the shortcomings and limitations of some existing methods for solving linear programming problems with fuzzy parameters are pointed out and new methods are proposed to overcome the shortcomings and limitations of existing methods.
Doctor of Philosophy (Mathematics)
Keywords: Fuzzy sets; Fuzzy linear programming